Developmental outcomes in children exposed to Zika virus in utero from a Brazilian urban slum cohort study. - Juan P Aguilar Ticona; Nivison Nery; Joseph B Ladines-Lim; Claudia Gambrah; Gielson Sacramento; Bruno de Paula Freitas; Joseane Bouzon; Jamary Oliveira-Filho; Ana Borja; Haritha Adhikarla; Magelda Montoya; Athena Chin; et al. (Public Library of Science (PLoS), 2021)
Background The prevalence of developmental alterations associated with in-utero Zika virus (ZIKV) exposure in children is not well understood. Furthermore, estimation of the Population Attributable Fraction (PAF) of developmental alterations attributed to ZIKV has not been performed due to lack of population-based cohorts with data on symptomatic and asymptomatic ZIKV exposures and an appropriate control group. The aim of this study was to characterize neurodevelopmental outcomes of children at 11 to 32 months of age with intrauterine ZIKV exposure and estimate the PAF of alterations secondary to ZIKV exposure. Methodology/principal findings We performed a cohort of biannual community-based prospective serosurveys in a slum community in Salvador, Brazil. We recruited women participating in our cohort, with a documented pregnancy from January 2015 to December 2016 and children born to those mothers. Children were classified as ZIKV exposed in utero (born from women with ZIKV seroconversion during pregnancy) or unexposed (born from women without ZIKV seroconversion or that seroconverted before/after pregnancy) by using an IgG monoclonal antibody blockade-of-binding (BoB). We interviewed mothers and performed anthropometric, audiometric, ophthalmological, neurologic, and neurodevelopmental evaluations of their children at 11 to 32 months of age. Among the 655 women participating in the cohort, 66 (10%) were pregnant during the study period. 46 (70%) of them completed follow-up, of whom ZIKV seroconversion occurred before, during, and after pregnancy in 25 (54%), 13 (28%), and 1 (2%), respectively. The rest of women, 7 (21.2%), did not present ZIKV seroconversion. At 11 to 32 months of life, the 13 ZIKV-exposed children had increased risk of mild cognitive delay (RR 5.1; 95%CI 1.1-24.4) compared with the 33 children unexposed, with a PAF of 53.5%. Exposed children also had increased risk of altered auditory behavior (RR 6.0; 95%CI 1.3-26.9), with a PAF of 59.5%. Conclusions A significant proportion of children exposed in utero to ZIKV developed mild cognitive delay and auditory behavioral abnormalities even in the absence of gross birth defects such as microcephaly and other neurodevelopmental domains. Furthermore, our findings suggest that over half of these abnormalities could be attributed to intrauterine ZIKV exposure.